DETERMINATION OF INFLUENCE AND DIFFERENCES IN SPECIFIC PROFESSIONAL SAMPLE OF EXAMINEES - Aleksandar Simeonov; Zoran Radikj; Ratko Pavlovikj (Faculty of Education – University of Travnik, Bosnia & Herzegovina, 2017)
In a sample of 80 respondents, population special forces, divided into three subsample age: the first group of 27 to the age of 25 years, the second group of 28 aged between 26-30 years and the third group of 25 aged 31 - 36, made a study of motor abilities as part of the program structure to carry out the unit. In this research procedure isolated four motor variables: push-ups, abdominal muscles, pull-ups and running the 3000m. For each of the variables according to the number of the engine under test and the time for running the 3000 meters obtain credits. In the research procedure was used descriptive method, classification of frequencies of the motor performance and determining, the impact of the criterion on prognostic variables and determining the differences between respondents. The results of descriptive statistics, we can conclude that the variables push-ups, sit-ups and points, there are major differences in the tests, which bear witness high rates of standard deviation, showing a greater deviation from the average value, and coefficients of variability that tell us higher percentage of variation of the standard deviation from the mean. The results of the regressive analysis show statistical significance, that motor variables as significant prognostic influence criteria variable, which tells us that the points scale better evaluates the results and is a good representative as a criteria for achieved results. As a general conclusion of the research in three subsample respondents according to age, we can conclude that there are no statistically significant differences between them, and the majority of respondents are in good physical preparation.
Keywords: motor skills; motor tests; variables; analysis; regression; influence; differences.